Impact of National Institutes of Health Gastrointestinal PROMIS Measures in Clinical Practice: Results of a Multicenter Controlled Trial. (November 2016) - Almario, Christopher V; Chey, William D; Khanna, Dinesh; Mosadeghi, Sasan; Ahmed, Shahzad; Afghani, Elham; Whitman, Cynthia; Fuller, Garth; Reid, Mark; Bolus, Roger; Dennis, Buddy; Encarnacion, Rey; et al.
Abstract : OBJECTIVES: The National Institutes of Health (NIH) created the Patient Reported Outcomes Measurement Information System (PROMIS) to allow efficient, online measurement of patient‐reported outcomes (PROs), but it remains untested whether PROMIS improves outcomes. Here, we aimed to compare the impact of gastrointestinal (GI) PROMIS measures vs. usual care on patient outcomes. METHODS: We performed a pragmatic clinical trial with an off‐on study design alternating weekly between intervention (GI PROMIS) and control arms at one Veterans Affairs and three university‐affiliated specialty clinics. Adults with GI symptoms were eligible. Intervention patients completed GI PROMIS symptom questionnaires on an e‐portal 1 week before their visit; PROs were available for review by patients and their providers before and during the clinic visit. Usual care patients were managed according to customary practices. Our primary outcome was patient satisfaction as determined by the Consumer Assessment of Healthcare Providers and Systems questionnaire. Secondary outcomes included provider interpersonal skills (Doctors' Interpersonal Skills Questionnaire (DISQ)) and shared decision‐making (9‐item Shared Decision Making Questionnaire (SDM‐Q‐9)). RESULTS: There were 217 and 154 patients in the GI PROMIS and control arms, respectively. Patient satisfaction was similar between groups ( P >0.05). Intervention patients had similar assessments of their providers' interpersonal skills (DISQ 89.4±11.7 vs. 89.8±16.0, P =0.79) and shared decision‐making (SDM‐Q‐9 79.3±12.4 vs. 79.0±22.0, P =0.85) vs. controls. CONCLUSIONS: This is the first controlled trial examining the impact of NIH PROMIS in clinical practice. One‐time use of GI PROMIS did not improve patient satisfaction or assessment of provider interpersonal skills and shared decision‐making. Future studies examining how to optimize PROs in clinical practice are encouraged before widespread adoption.